2017
DOI: 10.1002/chem.201703305
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Folate‐Receptor‐Positive and ‐Negative Cells Using a Substrate‐Mimicking Fluorescent Probe

Abstract: Diagnosis and therapy exploiting overexpressed receptors on the cell surface is one important strategy in medicine. Determination of the over expression level of a particular receptor is prerequisite for it to be of clinical use. Differentiation between FR-positive (FR=folate receptor) and -negative cells via fluorescence microscopy using a substrate mimetic fluorophore is presented in this work. The strategy adopted here is not the classical FA-conjugated (FA=folic acid) fluorescent probe but a small and envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…On the contrary to this, MFCSNPs-FA-CHI-5FU nanocarriers showed a noteworthy cell antiproliferative potential toward HeLa (51.54% cell viability at 200 μg/mL) and the activity was also found to be comparable with the cytotoxicity of free 5-FU toward the HeLa cell line. A375 cells are the folate receptor (FR) negative cell line and always used as a FR negative control, while the FR expression on the cell surface of MCF-7 is moderate as compared to the HeLa cells which have highly expressed FR markers. , Therefore, in the present study, synthesized MFCSNPs-FA-CHI-5FU nanocarriers that are folic acid conjugated show considerable cell cytotoxicity against HeLa cells. The obtained cytotoxicity of the MFCSNPs-FA-CHI-5FU nanocarriers is almost same in the A375 and MCF-7 because, although the MCF-7 cells show moderate FR expression, the IC 50 of 5-FU against the MCF-7 cell line is at higher range.…”
Section: Resultsmentioning
confidence: 94%
“…On the contrary to this, MFCSNPs-FA-CHI-5FU nanocarriers showed a noteworthy cell antiproliferative potential toward HeLa (51.54% cell viability at 200 μg/mL) and the activity was also found to be comparable with the cytotoxicity of free 5-FU toward the HeLa cell line. A375 cells are the folate receptor (FR) negative cell line and always used as a FR negative control, while the FR expression on the cell surface of MCF-7 is moderate as compared to the HeLa cells which have highly expressed FR markers. , Therefore, in the present study, synthesized MFCSNPs-FA-CHI-5FU nanocarriers that are folic acid conjugated show considerable cell cytotoxicity against HeLa cells. The obtained cytotoxicity of the MFCSNPs-FA-CHI-5FU nanocarriers is almost same in the A375 and MCF-7 because, although the MCF-7 cells show moderate FR expression, the IC 50 of 5-FU against the MCF-7 cell line is at higher range.…”
Section: Resultsmentioning
confidence: 94%
“…Also, very slight red fluorescence was observed from the nucleus of BHK‐21 cells as compared to HeLa cells, which suggests a greater release of Dox in the cytoplasm of HeLa cells along with the penetration of released Dox into the nucleus due to its DNA intercalation properties. The folate receptor is considered to be a biomarker for cancer as it is overexpressed in several tumors [17a,37] . It has been a popular choice for therapeutic and diagnostic tools to achieve targeted delivery to cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…The specificity of cit-AuNPs-MPA/Si-NH 2 QDs/Con A as a smart material was investigated using HEK 293 normal cells, in which glycan receptors are not expressed on the membrane of the cells. 40 HEK 293 cells were incubated with the cit-AuNPs-MPA/Si-NH 2 QDs/Con A NPs to check their possible attachment to the cell surface. The obtained results confirmed that the Con A-functionalized cit-AuNPs-MPA/Si-NH 2 QDs nanocomposite cannot be captured by the low-expressed normal cells; the obtained results confirmed the differentiating ability of cit-AuNPs-MPA/Si-NH 2 QDs/Con A NPs between HEK 293 glycan receptor-negative cells and glycan receptor-positive MCF-7 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…normal cells, in which glycan receptors are not expressed on the membrane of the cells 40. HEK 293 cells were incubated with the cit-AuNPs-MPA/Si-NH 2 QDs/Con A NPs to check their possible attachment to the cell surface.…”
mentioning
confidence: 99%